INTEGRATION OF INTRADISCIPLINARY TOPICS AND GEOGRAPHY IN THE TEACHING PROCESS OF TECHNOLOGY - M. S Kazimov (Образование и наука)
The research paper deals with complex approach to integrative learning of most relevant themes of the subject of Geography and the subject of Technology. Within the section «Technology of woodworking», which is part of subject of Technology, it is important to teach students the form of coherent information on the processing of wood, properties of selected tree breeds, features of the installation details, types of trees used for timber production, the origin of trees, and expansion of trees over areas. All these knowledge should be delivered to students through an integrative teaching process.Methods. Study method of this research paper involves two main methods: statistical analysis as quantitative research method and literature review as qualitative research method. Based on statistical analysis the researcher tries to find out detailed information regarding facts that are used in the subject of Technology. Whereas literature review is referred in order to investigate the possibility of integrating the two subjects for the sake of better delivery of necessary knowledge to students. Moreover, as supporting research methods systematic approach to educational issues on the purpose of examining complicated issues precisely.Results. The study revealed possible emergence of interdisciplinary connections while realising integrative teaching of «Technology of woodworking» together with the teaching of Geography. Moreover, the research paper recommended giving priority to various collaborative learning processes while carrying out integrative teaching. Furthermore, the author provides detailed information about features and types of trees eligible for timber production, and also indicates statistical data about trees which are considered relevant information in the teaching of «Technology of woodworking».Scientific novelty. The implication and scientific novelty of the article contributes a lot to contemporary educational approaches one of which is integrative teaching or, in another word, inter-curricular integration. Thanks to the integrated teaching of Technology and Geography, it is possible for the students to learn the subject comprehensively and much better because integration creates conditions for the development of logical thinking and the formation of ability of independent thinking of students. Moreover, integrative teaching of subjects contributes to the build close relationship between the subjects and themes which have a positive impact on the creation of a dialogue and mutual understanding between teachers and students. This fact, in its turn, lays the foundation for an integrative approach to the study of the subjects.Practical significance. The results and suggestion of this research paper are considered appropriate to be used when creating integrative learning of Technology and Geography in vocational schools and when studying interdisciplinary issues for vocational schools.